АCADEMIC B.ORUZVAEVA IS A FAMOUS IEXICOGRAPHER (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the contributions of academician B.O. Oruzbaeva, a prominent lexicographer and the founder of Kyrgyz terminology. She studied the structure of dictionaries in Kyrgyz linguistics. Also was noted about the structure of creating a dictionaries, order issues of them, language pecularities, the structure of Russian-Kyrgyz dictionaries.
Keywords: terminology, Kyrgyz terminology, lexicography, lexicographer, terminological dictionary, encyclopedic dictionary, linguistic dictionary, dictionary